Forest cover influences occurrence of mammalian carnivores within Brazilian Atlantic Forest - Regolin A.L. (2017)
© 2017 American Society of Mammalogists.Habitat fragmentation reduces biodiversity and affects ecological processes that are fundamental for maintaining ecosystem services. We investigated how landscape structure - percent forest cover, patch density, percent cover by edge, perimeter-area ratio, and spatial heterogeneity - affects the diversity of mammalian carnivores at multiple extents within 22 Atlantic Forest landscapes. We hypothesized that 1) species richness of carnivores is positively related to forest cover; and 2) the occurrence of species will vary according to its sensitivity to forest loss and its preference for forest or open areas. Species richness, composition, and occurrence of mammalian carnivores were correlated with several landscape structure metrics. Due to a high correlation among the metrics, we adopted forest cover as the principal predictor variable. We compared a forest cover model to a null model using Akaike Information Criterion (AICc), and evaluated other fragmentation metrics using a redundancy analysis. Carnivore species richness was positively related to forest cover and negatively associated with other fragmentation metrics. However, the responses to landscape structure differed among species, possibly due to their differences in habitat use. Landscape configuration is an important factor influencing carnivore species composition. Forest cover can explain some, but not all, carnivore species occurrence. Our results reinforce the protection of forests as fundamental to the conservation of carnivore species and the ecological processes in which they participate.